Sex differences in behavioral and neurochemical effects of gonadectomy and aromatase inhibition in rats. - Kokras, N; Pastromas, N; Papasava, D; de Bournonville, C; Cornil, C A; Dalla, C (Psychoneuroendocrinology, 2018)
Aromatase inhibitors, which are widely used for the treatment of estrogen-dependent cancers, have been associated with psychiatric side effects ranging from mania to depression. In the present study, we investigated sex differences in the behavioral and neurochemical effects of aromatase inhibition on male and female, sham-operated or gonadectomized adult rats. Three weeks after surgery, rats received chronic treatment with the aromatase inhibitor letrozole or vehicle and were then subjected to the open field test, which assesses general activity. Half of the subjects were subsequently exposed to the stressful procedure of the forced swim test (FST), which is also a test of antidepressant activity. Aromatase activity was analyzed in the hypothalamus and testosterone and corticosterone were assayed in the blood serum of all rats. The hippocampus and prefrontal cortex (PFC) were analyzed for monoamine (noradrenaline, dopamine and serotonin), as well as amino acid (GABA, glutamate, glycine, taurine, alanine and histidine) levels. The observed decrease in hypothalamic aromatase activity confirmed the efficacy of letrozole treatment in both sexes. Moreover, letrozole enhanced testosterone levels in sham-operated females. In the open field test, females were overall more active and explorative than males and gonadectomy eliminated this sex difference. In the FST, females exhibited overall higher immobility than males and gonadectomy further enhanced this passive behavior in both sexes. However, sustained aromatase inhibition had no effect on open field and FST behaviors. Head shakes during FST, which were fewer in females than in males, were reduced by castration in males and by letrozole treatment in ovariectomized females, suggesting a role of testosterone and extra-gonadal estrogens in the expression of this behavior. Sustained aromatase inhibition also decreased noradrenaline and the dopaminergic turnover rates [DOPAC/DA, HVA/DA] in the hippocampus and PFC of male and female rats, irrespectively of gonadectomy. Moreover, letrozole treatment enhanced the serotonergic turnover [5HIAA/5HT] rate in the hippocampus of males and females, irrespectively of gonadectomy. Amino acid levels were not influenced by letrozole, but sex differences were demonstrated with higher levels in the PFC of females vs. males. Present findings suggest that the neuropsychiatric effects of aromatase inhibition can be attributed to the inhibition of extragonadal estrogen synthesis, presumably in the brain, and could be further associated with serotonergic and catecholaminergic changes in brain regions involved in mood and cognition. Importantly, present data could be linked with the neurobiology of affective side-effects in post-menopausal women receiving aromatase inhibitors.
Keywords: Animals; Antidepressive Agents; Aromatase; Aromatase inhibitors; Behavior, Animal; Brain; Castration; Corticosterone; Depression; Female; Hippocampus; Letrozole; Male; Nitriles; Orchiectomy; Ovariectomy; Prefrontal Cortex; Rats; Rats, Wistar; Serotonin; Sex Characteristics; Testosterone; Triazoles